Riskscapes revisited - Exploring the relationship between risk, space and practice - Müller-Mahn, Detlef; Everts, Jonathan; Stephan, Christiane (ERDKUNDE, 2018)
The concept of riskscapes refers to temporalspatial phenomena that relate risk, space and practice. It links the material dimension of potential physical threats, the discursive dimension of how people perceive, communicate and envision risks, and the dimension of agency, i.e., how people produce risks and manage to live with them. Located at the interface of these three dimensions, riskscapes are co-produced by collective imaginations of ‘landscapes of risk’, and ensuing coordinated action. The paper revisits the concept as it was first outlined by the present authors (Müller-Mahn and Everts 2013), discusses its applications in risk research, and highlights its key arguments with respect to four points: the spatial dimension of risk, the practices of risk-taking, the relevance of group-specific risk perspectives and the plurality of risk settings. Building upon these four key arguments, the paper explores the concept further and suggests new lines of argumentation by focusing on two additional aspects that have so far been given little attention. First, it suggests a systematic reflection on power relations, especially with regard to the role of the state. Second, it discusses the embeddedness of riskscapes in temporal frames pertaining to different actors, groups and power structures. The article further explores the relation between risk and the future, and how practices of future-making shape the emergence of riskscapes.